THE RELATIONSHIP OF CHEWING GUM WITH TEMPOROMANDIBULAR JOINT DISORDERS: RAPID REVIEW - Evy Carolina Choandra; Rasmi Rikmasari; Seto Pramudita (Interdental Jurnal Kedokteran Gigi (IJKG), 2023)
Introduction: Temporomandibular joint disorder are reported to affect 50 until 75% of the adult population and can affect an individual’s quality of life. The etiology of this disorder is multifactorial; it can be caused by parafunctional habit, chewing gum. 13% of adolescents and adults were reported chewing gum regularly. This study aims to determine the relationship between chewing gum and temporomandibular joint disorder. Review: This study was conducted using the rapid review method with screening and search referring to the Preferred Reporting Items for Systematic Review and Meta-analysis (PRISMA) guidelines. Article searches were performed using keywords and inclusion criteria in the Google Scholar, PubMed, and ScienceDirect databases. A total of 4 articles using observational research methods were included. Evaluation of the habit of chewing gum was carried out using questionnaires and interviews, while the paramenters used to evaluate temporomandibular joint disorders were anamnesis and clinical examination based on the Research Diagnostic Criteria for TMD (RDC/TMD). Three articles indicated that there was a significant association between gum chewing and temporomandibular disorder, whereas 1 article concluded that further studies on this topic were necessary. The heterogeneity that occurs can be caused by differences in sample characteristics and methods. Conclusion: The habit of chewing gum can cause temporomandibular joint disorders